Knowledge intensive business services: innovation and occupations. Issue 3 (30th May 2019) - Miles, Ian Douglas; Belousova, Veronika; Chichkanov, Nikolay
Abstract : Purpose: The literature on knowledge-intensive business services (KIBS) shows them to be major innovators; this is confirmed with recent data, which the authors use to examine the various types of innovation that KIBS undertake. The implications for employment and work in highly innovative industries are important topics for analysis, not least because we are in a period where dramatic claims are being made as to the implications of new technologies for professional occupations. Thus, this paper aims to address major debates and conclusions concerning innovation patterns in KIBS and the evolving structures of professional and other work in these industries. Design/methodology/approach: This essay combines literature review with presentation and discussion of statistics that throw light on the patterns of innovation that characterise KIBS. The authors also consider data that concern trends in the organisation of work in these industries; while the focus is mainly on KIBS firms, they also pay some attention to KIBS-like work in other sectors. Even though KIBS are distinctive industries in modern economies, these analyses can be related to more general studies of, and forecasts about, changes in work organisation. Findings: The authors show that innovation patterns and employment structures vary substantially across different types of KIBS, with the distinction between technological, professional and creative KIBS proving to be useful for capturing these differences. The authors are also able to demonstrate important long- and medium-term trends in the structure and activities of the KIBS industries. In particular, data clearly demonstrate the increasing share of professional as against associate and clerical workers in most KIBS. Evidence also suggests that polarisation trends across the economy are mirrored, and in some cases amplified, in KIBS. The future prospects for employment in KIBS, and for professional work in particular, are seen to involve multiple factors, which together may bring about substantial change. Research limitations/implications: The study involves literature review and industry-level statistical analysis. Future work would benefit from firm-level analysis and validation and explication of results via consultation with practitioners and users of KIBS. Some puzzling variations across countries and sectors will need to be explored with national and sectoral experts. Practical implications: Research into KIBS activities, and their future, should make more use of the extensive statistics on employment and other structural features of the industries that have become available in recent years. KIBS firms and practitioners will need to take account of the forces for change that are liable to restructure their activities. Originality/value: The literature on KIBS has been concentrated on a rather narrow range of issues, while analysis of the current contributions and future development of the industries requires attention to a wider range of topics. This paper suggests how these topics may be investigated and their implications explored and presents results of enquiries along these lines.